2013
DOI: 10.1088/0004-637x/774/1/9
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Evolution and Photoevaporation of Circumstellar Disks Due to External Far Ultraviolet Radiation Fields

Abstract: This paper explores the effects of FUV radiation fields from external stars on circumstellar disk evolution. Disks residing in young clusters can be exposed to extreme levels of FUV flux from nearby OB stars, and observations show that disks in such environments are being actively photoevaporated. Typical FUV flux levels can be factors of ∼ 10 2 − 10 4 higher than the interstellar value. These fields are effective in driving mass loss from circumstellar disks because they act at large radial distance from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 48 publications
4
105
0
Order By: Relevance
“…Previous observational studies of Herbig Ae/Be stars suggested that photoevaporation destroys primordial discs around high-mass stars within less than 1 Myr (Hillenbrand et al 1998;Hernández et al 2005;Alonso-Albi et al 2009;Gorti et al 2009). A short survival timescale of less than 1-3 Myr in UV-rich clusters is confirmed by numerical simulations of disc survival (Anderson et al 2013, and references therein). When FUV, EUV, and X-ray luminosities are taken into account, stars with M < 3 M have simulated disc lifetimes of several 10 6 years.…”
Section: Discs In the Arches Clustermentioning
confidence: 62%
See 1 more Smart Citation
“…Previous observational studies of Herbig Ae/Be stars suggested that photoevaporation destroys primordial discs around high-mass stars within less than 1 Myr (Hillenbrand et al 1998;Hernández et al 2005;Alonso-Albi et al 2009;Gorti et al 2009). A short survival timescale of less than 1-3 Myr in UV-rich clusters is confirmed by numerical simulations of disc survival (Anderson et al 2013, and references therein). When FUV, EUV, and X-ray luminosities are taken into account, stars with M < 3 M have simulated disc lifetimes of several 10 6 years.…”
Section: Discs In the Arches Clustermentioning
confidence: 62%
“…For Herbig Ae/Be stars in nearby OB associations, Hernández et al find intermediate-mass disc fractions of only 2-5% at ages 3-10 Myr. In particular in the dense environment of starburst clusters such as the Arches and Quintuplet clusters near the Galactic centre, star-disc interactions (Olczak et al 2012) and the external UV radiation field (Anderson et al 2013;Fatuzzo & Adams 2008;Adams et al 2004;Scally & Clarke 2001;Richling & Yorke 2000;Johnstone et al 1998) might contribute to an even more rapid depletion of circumstellar material.…”
Section: Circumstellar Disc Survivalmentioning
confidence: 99%
“…In this case, the viscous timescale decreases with time and hence the clearing is accelerated. This effect results in the disc clearing an order of magnitude faster than t w (Clarke 2007, Anderson et al 2013 and it is obvious that in this case most of the disc mass is cleared by accretion rather than photoevaporation. Nevertheless photoevaporation is playing a decisive role in preventing disc spreading and thus keeping the viscous timescale short.…”
Section: The Effect Of Mild Fuv Fields In Sparse Star Forming Environmentioning
confidence: 98%
“…In this work, we adopt a out = 50 AU as a characteristic size of a typical protoplanetary disk (e.g., Anderson et al 2013). With these specifications, the Hamiltonian takes on a simple form:…”
Section: Dynamics Of the Stellar Spin Axismentioning
confidence: 99%